Role of Lewis Acids of MIL-101(Cr) in the Upgrading of Ethanol to n-Butanol - Zhou, Jian; Tong, Yuqin; He, Yaohui; Tu, Pengxiang; Xue, Bing; Cheng, Yunhui; Cen, Jie; Zheng, Yifan; Ni, Jun; Li, Xiaonian (Frontiers in Chemical Engineering, 2020)
The upgrading of bioethanol to n-butanol has recently been a focus of considerable attention due to the advantages of n-butanol over bioethanol as a sustainable fuel. The efficiency of this reaction is highly dependent on the development of catalysts, where understanding how catalysts perform is essential. However, traditional catalysts are normally composed of several kinds of active sites that work together synergistically in reactions, making it challenging to identify the role that individual active sites play. Herein, we synthesized three chromium-based MOFs ((MIL-101(Cr), where MIL stands for Matériaux Institut Lavoisier) with different Lewis acidities but without any basic sites. The linear relationship between Lewis acidities and their dehydration and condensation abilities suggests that there is a competition between the ethanol dehydration to diethyl ether and acetaldehyde condensation on Lewis acids. Upon the introduction of Pd, the Lewis acidity also dominates the particle size of Pd and then the dehydrogenation and hydrogenating abilities of catalysts.